Advocacy Coalition Framework in Fixing Road Transport Act 2018 of Bangladesh - Md. Jahid Hashan (South Asian Journal of Social Sciences and Humanities, 2025)
The Advocacy Coalition Framework (ACF), pioneered by Paul Sabatier and Hank Jenkins-Smith, provides a powerful analytical lens for understanding policy change in contested governance spaces. This study applies the ACF to examine the enactment of Bangladesh’s Road Transport Act 2018, a landmark policy reform that replaced the Motor Vehicle Ordinance of 1983 in response to the country’s escalating road safety crisis. The Act was catalyzed by nationwide student-led protests following the tragic deaths of two students in a road accident, revealing deep-rooted governance failures, public discontent, and entrenched opposition from transport sector stakeholders. This research identifies two dominant advocacy coalitions: the “We Want Safe Roads” coalition, comprising students, civil society, and the media, advocating for stricter traffic laws and greater accountability; and the Road Transport Workers’ Federation coalition, resisting regulatory changes to protect industry interests. The study examines the interplay between coalition strategies, policy brokers, and external system events, demonstrating how public mobilization and media influence reshaped policy discourse and compelled legislative action. Findings underscore the incremental and conflict-driven nature of policy reform, revealing the complexity of institutional resistance, stakeholder negotiations, and enforcement challenges in the policymaking process. This case reinforces the relevance of the ACF in analyzing policy shifts in highly politicized environments and offers broader insights into the dynamics of advocacy coalitions in developing governance contexts.